Demographic profile of patients and clinical characteristics of dental emergencies at the outpatient clinic of a Brazilian Dental School - Andrea Cardoso PEREIRA; Ana Carolina Correia Laurindo de CERQUEIRA NETO; Alexandre Augusto ZAIA; Brenda Paula Figueiredo de Almeida GOMES; José Flávio Affonso de ALMEIDA; Adriana de Jesus SOARES (Faculdade São Leopoldo Mandic, 2018)
Objective: This retrospective study evaluated the demographic profile of patients and the clinical characteristics of dental emergencies in a brazilian university outpatient clinic. Methods: During the period from June 2013 to May 2014, data were collected from 1.345 clinical records. Chief complaint, gender, age, systemic alteration, clinical inspection of the affected tooth, pulp and periapical diagnosis, the type of procedure performed and whether there was the need for post-operative systemic medication. Data were analyzed using the SAS software and chi-square test was used to verify the presence or absence of statistical significance at a level of 5%. Results: Dental pain (53.3%) was the main reason why people attended the emergency service, that is, female patients (63.1%), aged 29-48 years old (42%), patients without systemic conditions (75%), and patients with decayed teeth (25%). In addition, involvement of lower molars (29.81%) and diagnosis of irreversible pulpitis (30.42%) were the most frequent findings. Emergency endodontic treatment (45.8%) was the most performed procedure. Irreversible pulpitis (30.4%) and pulp necrosis associated with acute apical periodontitis (21.9%) were the most frequent conditions requiring emergency endodontic treatment, and in most cases, there was no need for post-operative systemic medications (95.7%). Conclusion: The prevalence of endodontic emergencies during the period of one year emphasizes the need for more accurate diagnosis and the importance of providing this service to the population.